An Experimental Study to Evaluate the Anti-Diarrheal Activity of Bhuvaneshwara Rasa in Wistar Albino Rats (International Journal of Ayurveda and Pharma Research, 2021)
Atisara (Diarrhea) is most commonly encountered disease of the present era, due to unhealthy and irregular habits. Atisara (Diarrhea) finds a place as important disease in individual’s life as everyone suffers from it at least once in life time. Bhuvaneshwara rasa is a unique herbo-mineral formulation explained in Bhaishajya ratnavali indicated for all kinds of diarrhea cases. Bhuvaneshwara rasa is a potent formulation having Saindhava, Triphala, Yamani, Bilva peshika and Gruhadhooma.Materials and methods: Raw materials were screened and collected and the formulation selected for the present study Bhuvaneshwara rasa was prepared accordingly. Anti-diarrheal activity of Bhuvaneshwara rasa was evaluated experimentally in albino rats. Experimental study was conducted in 3 groups of animals for anti-diarrheal study each. Anti-diarrheal study was done by castor oil induced diarrhoea and castor oil induced enter-pooling method. Bhuvaneshwara rasa (test drug) and Loperamide are effective in controlling diarrheal episodes. Bhuvaneshwara rasa has shown significant Anti-diarrheal activity in both Castor oil -induced diarrhea and castor oil induced enteropooling, test drug effective than control.Result: Bhuvaneshwara rasa was prepared according to SOP. Test drug group have shown effect experimentally. Conclusion: Bhuvaneshwara rasa is a good anti-diarrheal drug. It can be administered in all types of Atisara.